Single Burr Hole and Drainage in Chronic Subdural Hematoma: Outcome in Consecutive 333 Cases - Roka, Yam B; Firoj, Afjal; Alok, Jha; Biprav, Lohani (Nepal Journal of Neuroscience, 2016)
Chronic subdural hematoma (CSDH) is a common neurosurgical disease with incidence 3 in 100,000 in general population. Recorded or trivial head injury is the most common cause of CSDH with several predisposing factors like alcoholism, coagulopathy, seizure disorder, cerebrospinal fluid shunts, metastases and vascular malformations. Bilateral CSDH are common in infants and interhemispheric subdural hematomas are often associated with child abuse. Coagulopathy and intracranial tumors have been associated with spontaneous CSDH. 86 % were males with 47% of CSDH on left followed by 35% in right and 61 cases (18%) were bilateral. The most common age group was 61 to 80 years (45%) followed by the 41 to 60 year group. During admission headache was the most common symptom followed by neurological deficits that include, loss of speech (65%), mono or hemiparesis (20%), quadreparesis (5%), bowel and bladder dysfunction and loss of memory or altered sensorium. Statistical analysis did not show any significant p value between the Age group, Sex, Side of CSDH or chronic alcoholism as independent variables affecting outcome. GCS at admission was the only factor that had significant p value in terms of outcome prediction. Although there are multiple comorbidities associated with CSDH this study found that except GCS there was no relation to age, side, sex, alcoholism, hypertension or diabetes in the outcome after surgery. Meticulous care to remove all the CSDH followed by use of drain is the most efficient way to manage CSDH. Nepal Journal of Neuroscience 13:35-42, 2016